Influence of ethanol/water ratio in ultrasound and high‐pressure/high‐temperature phenolic compound extraction from agri‐food waste. (31st October 2015) - Paini, Marco; Casazza, Alessandro A.; Aliakbarian, Bahar; Perego, Patrizia; Binello, Arianna; Cravotto, Giancarlo
Summary: The valorisation and management of agri‐food waste are currently hot investigation topics which probe the recovery of valuable compounds, such as polyphenols. In this study, high‐pressure/high‐temperature extraction (HPTE) and ultrasound‐assisted extraction (UAE) have been used to study the recovery of phenolic compounds from grape marc and olive pomace in hydroalcoholic solutions. The main phenolic compounds in both extracts were identified by HPLC‐DAD. Besides extraction yield (total polyphenol and flavonoid content) and the antiradical power, polyphenol degradation under HPTE and UAE has also been studied. HPTE with ethanol 75% gave higher phenolic extraction yields: 73.8 ± 1.4 mg of gallic acid equivalents per gram of dried matter and 60.0 mg of caffeic acid equivalents per gram of dried matter for grape marc and olive pomace, respectively. In this study, the efficient combination of ethanol/water mixture with HPTE or UAE has been used to enhance the recovery of phenolic compounds from grape marc and olive pomace. HPLC‐DAD showed that UAE prevents phenolic species degradation damage because of its milder operative conditions. Abstract : High‐pressure/high‐temperature extraction (HPTE) and ultrasound‐assisted extraction (UAE) have been used to enhance the recovery of phenolic compounds from grape marc and olive pomace.